Analisis Fitokimia Daun Sambung Nyawa Sebagai Kandidat Obat Herbal untuk Terapi Hipertensi Ringan - Nerdy Nerdy; Nilsya Febrika Zebua; Andre Aditya; Dea Amelia Adiatma; Ira Eka Fahira; Miska Raihana; Rijalul Ihsan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the phytochemical profile of Sambung Nyawa (Gynura procumbens) leaves as a potential herbal candidate for mild hypertension therapy using in silico methods. Plant samples were examined to identify active compounds documented in the PubChem database. The identified compounds were further analyzed using PASS Online to predict their pharmacological activities, ProTox-II to evaluate toxicity levels, and pkCSM to assess ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) characteristics. The findings reveal that several bioactive compounds present in Sambung Nyawa leaves demonstrate strong predicted anti-hypertensive activity accompanied by minimal toxicological risk. PASS Online analysis indicates potential mechanisms of action, including vascular receptor modulation and mild diuretic properties that may support blood pressure regulation. ProTox-II classification places most compounds in the low-toxicity category, while pkCSM predictions confirm acceptable bioavailability and favorable pharmacokinetic properties. Overall, these results provide a preliminary scientific foundation for the development of Gynura procumbens as an alternative herbal therapy for mild hypertension and support the need for further validation through in vitro and in vivo experimental studies.